2015
DOI: 10.1039/c4ta05246c
|View full text |Cite
|
Sign up to set email alerts
|

Perovskite solar cells: film formation and properties

Abstract: Perovskite solar cells have received considerable attention in recent years as a promising material capable of developing high performance photovoltaic devices at a low cost. Its high absorption coefficient, tunable band gap, low temperature processing and abundant elemental constituents provide numerous advantages over most thin film absorber materials. In this feature article, we discuss the current status of CH3NH3PbX3 (X = I, Br, Cl) based photovoltaic devices and provide a comprehensive review of CH3NH3Pb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
279
0
11

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 414 publications
(305 citation statements)
references
References 118 publications
(196 reference statements)
3
279
0
11
Order By: Relevance
“…As discussed previously 14,15 , perovskites were originally viewed as a curious replacement to dye molecules in mesoscopic sensitized solar cells, due to its high absorption coefficient and broad absorption spectrum (Fig. 2a) 9 .…”
Section: Photovoltaics (Pvs)mentioning
confidence: 99%
See 1 more Smart Citation
“…As discussed previously 14,15 , perovskites were originally viewed as a curious replacement to dye molecules in mesoscopic sensitized solar cells, due to its high absorption coefficient and broad absorption spectrum (Fig. 2a) 9 .…”
Section: Photovoltaics (Pvs)mentioning
confidence: 99%
“…To date, tremendous efforts have been devoted to optimizing the perovskite crystallization and film formation in order to obtain highly crystalline and pinhole free perovskite thin films. Several review papers discuss the details of the differing growth methods 14,15 . Recently, perovskite thin films with full surface coverage and large polycrystalline domains (Fig 1g) have been achieved on large area by doctor-blade coating the precursor inks on hot substrates 16 , resulting in impressive device efficiencies.…”
Section: Versatile Forms Of Metal Halide Perovskitesmentioning
confidence: 99%
“…[87][88][89] While solar cells with record PCEs can be achieved without good control of the perovskite crystallization, this generally leads to films with large morphological deviations, leading to large PCE fluctuations in the resulting devices. [90] In this part of the review, we will discuss the reports on reproducible PCE and solar cell parameters. It should be noted that the reproducibility we are referring to is considered as a narrow scatter of PCE and solar cell parameters of PSCs processed under the same conditions.…”
Section: Reproducibility Of Perovskite Materialsmentioning
confidence: 99%
“…[90,222] As the structure is soluble in water, the presence of humidity during film processing can significantly influence the thin film morphology and can lead to improved solar cell performance. [3,46,223] However, when fully-formed perovskite solar cells are exposed to air with a water-vapor content above 50% at room temperature, a loss in performance is incurred.…”
Section: Moisturementioning
confidence: 99%
“…It has been reported that the surface roughness at the organic/perovskite interface is directly linked to the charge extraction and recombination [4,5]. We further examined using a BHJ layer with the same weight ratio may be a main reason for the efficiency decrease.…”
Section: Articlesmentioning
confidence: 99%